Enhancing Integer Arithmetic Understanding in Fourth-Grade Students Through Cooperative Learning and Multisensory Media - Dasiyem Dasiyem; Ester Julinda Simarmata; Rosdiana Samosir (Departement of Mathematics Education, 2024)
This research analyzes the impact of adopting the Numbered Head Together (NHT) approach, paired with colored bead medium, on the comprehension of integer arithmetic among fourth-grade pupils. The study occurs in two cycles, adopting a comprehensive approach that incorporates planning, action, observation, and reflection. The research intends to evaluate the effectiveness of this new teaching style in increasing student engagement, collaboration, and academic success. The initial observations suggest a common dependence on traditional teaching approaches in mathematics education, resulting in decreased student engagement and poor academic performance. The intervention teaches the NHT technique, emphasizing cooperative learning, and using colorful bead medium to address problems related with integer arithmetic comprehension. The physical and visible aspect of the media attempts to adapt to varied learning styles and boost the accessibility of abstract mathematical concepts. In conclusion, the study recommends for a radical shift in mathematics education, asking educators to adopt student-centric, cooperative learning techniques, and inventive teaching tools. The favorable outcomes seen in this research underline the potential for such novel techniques to increase academic achievement and contribute to overall student development. This research serves as a call to action for educators to adapt and innovate in response to growing educational requirements.